Cleopatra - Hoobler, Dorothy; Hoobler, Thomas (Bogota, Colombia : Cinco, 1987)
Text in Spanish. A biography of the Egyptian queen who gained and maintained power over her kingdom by beguiling Julius Caesar and Marc Antony.
5-8
5-8
Keywords: Kings, queens, rulers, etc; Spanish language materials; Cleopatra, Queen of Egypt, d. 30 B.C.; Cleopatra, Queen of Egypt, d. 30 B.C; Egypt -- Kings, queens, rulers, etc; Spanish language